Foundations of the Principles of Language Learning in the Peruvian National Curriculum - Fernandez Heredia, Ritchar Walter (2021)
In the present monograph work we can specify After having studied the principles of the Peruvian National Curriculum. •From the contrast between traditional linguistics and contemporary linguistics we can say that the traditional approaches of linguistics were necessary for the existence of the present-day linguistic theories that support the nature of language of language teaching methodology. I assume that contemporary linguistic currents have to do with generative grammar, cognitive linguistics, pragmatics and text linguistics. • The psychological foundations of English language teaching in the National Curriculum has to do with the different learning theories that support the Communicative language teaching and the National Curriculum. • The Communicative language teaching is the product of the efforts done from the linguistic perspective and from the psychological perspective as a way to implement the • National Curriculum around the world. • The Peruvian National Curriculum hast taken the contributions from the psychological perspective such as the cognitive psychology, constructivism and socioconstructivism and the contribution of many other sources. Also, it has the contribution of linguistics that takes into account the perspective of functional linguistics, pragmatics, cognitive linguistics, text linguistics and many other sources.